ANALISIS KEBERLANJUTAN EKOWISATA MANGROVE MENGKAPAN SIAK - Mufidah Dwi Suci; Rasoel Hamidy; Ridwan Manda Putra (Jurnal Ilmu Lingkungan, 2022)
Mangrove Ecotourism Management of Mengkapan Siak which has potential as an ecotourism area is currently experiencing stagnation in its development. The management of mangrove ecotourism in Mengkapan is still sectoral and has not been based on multi-sectoral and multi-dimensional considerations. This study aims to identify the condition of the mangrove ecotourism area by integrating multidimensional aspects (ecological, economic, socio-cultural, legal-institutional and infrastructure-technology) to be able to analyze the sustainability index of each dimension of mangrove ecotourism management, which will then be obtained sensitive attributes that are the key in the formulation of the mangrove ecotourism management strategy. This research was conducted using quantitative and qualitative approaches with survey methods, literature studies and interviews. The data obtained will be analyzed using Rap-Mangrove Analysis which aims to determine the sustainability status of mangrove ecotourism and leverage analysis to determine the sensitive attributes of each dimension. The results obtained that the index value of the ecological dimension is 48.20% (less sustainable), the economic dimension is 37.00% (less sustainable), the socio-cultural dimension is 78.60 (very sustainable), the legal-institutional dimension is 57.30 (sufficiently sustainable) and the infrastructure-technology dimension of 68.70 (sufficiently sustainable). Therefore, the development strategy that can be carried out is the rehabilitation of the mangrove ecosystem, increasing education to the local community, involving all stakeholders, as well as compiling and establishing standard management rules with legal force.